2015
DOI: 10.3389/fpubh.2015.00225
|View full text |Cite
|
Sign up to set email alerts
|

A Selected Review of the Mortality Rates of Neonatal Intensive Care Units

Abstract: IntroductionNewborn babies in need of critical medical attention are normally admitted to the neonatal intensive care unit (NICU). These infants tend to be preterm, have low birth weight, and/or have serious medical conditions. Neonatal survival varies, but progress in perinatal and neonatal care has notably diminished mortality rates. In this selected review, we examine and compare the NICU mortality rates and etiologies of death in different countries.MethodsA literature search was conducted in Ovid MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 34 publications
6
50
0
1
Order By: Relevance
“…The VLBW survival in our unit was significantly less than that reported in the VON [www.vtoxford.org] for the same period (69.1% vs. 85.6%). Neonatal mortality rates among different neonatal units are highly variable, but the rates reported in the present study are within the reported range for developing nations [3]. The current neonatal survival rates are better than those reported from NICUs in The Gambia [4] and Ethiopia [15], but worse than those reported from a NICU in Thailand [16].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The VLBW survival in our unit was significantly less than that reported in the VON [www.vtoxford.org] for the same period (69.1% vs. 85.6%). Neonatal mortality rates among different neonatal units are highly variable, but the rates reported in the present study are within the reported range for developing nations [3]. The current neonatal survival rates are better than those reported from NICUs in The Gambia [4] and Ethiopia [15], but worse than those reported from a NICU in Thailand [16].…”
Section: Discussionsupporting
confidence: 46%
“…This is particularly true when using data from a high-income country to address problems experienced in low-to middle-income countries (LMICS). A recent review of the mortality rates in neonatal intensive care units showed that the rate varied considerably between different countries [3]; the mortality rate was generally high, but greater in developing than developed countries. Issues such as the lack of antenatal care and inadequate health facilities are the causes of neonatal mortality in LMICS.…”
Section: Introductionmentioning
confidence: 99%
“…Those who had neonatal sepsis were nearly two times increase risk of mortality as compared to those who did not have sepsis. This finding is supported by a result in developed and developing country [19] [48] [7], [49] , [50] [51], ( [52], [53]. The possible reason might be due to newborns have many physiologic challenges when adapting to the extrauterine environment which might contributed to common problem like immature immunity, RDS., neurologic, cardiovascular, hematologic, nutritional, gastrointestinal and poor thermoregulation which farther increase risk of sepsis and mortality.…”
Section: Discussionmentioning
confidence: 53%
“…Globally, the neonatal mortality rate (NMR) is declined from 49 % to 19%, but slower than under five mortality rate (dropped by 60%) .Of all death of under-five , 40% were attributed with new born death [5] in which close to 1 and 2 million deaths occur on the day of birth, and in the first week of life respectively [6]. A review of 20 studies also indicated that the total NMR greatly varied between developed (4 to 46% ) and developing (0.2 to 64.4%) countries [7]. Despite this, NMR shares the highest proportion of under-five mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is significant reduction in under five mortality rates but newborn mortality have reduced much slowly. [2][3][4] Prematurity, birth asphyxia and infections are three important causes of neonatal deaths.…”
Section: Introductionmentioning
confidence: 99%